Pengaruh Active Learning Method terhadap Peningkatan Kebugaran Jasmani Siswa Ekstrakurikuler Karate - Gholiyah Puteri Virgie; Afifan Yulfadinata; Junaidi Budi Prihanto (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to explore the impact of Active Learning methods on improving the physical fitness of students participating in karate extracurricular activities at MTSN 3 Sidoarjo. This study applies a quantitative approach with a quasi-experimental design using the One Group PreTest- PostTest model. A total of 26 students who actively participated in karate extracurricular activities were used as research samples. The instrument used was the Multistage Fitness Test to measure VO2Max as an indicator of cardiorespiratory fitness. Data analysis using the Wilcoxon test was performed because the Pre-Test data was not normally distributed. The results of this study showed a significant increase in VO2Max values, where the pre-test median of 27.95 increased to 36.00 in the post-test. The Wilcoxon test produced a p-value < 0.05, indicating a significant difference between before and after the treatment. These findings indicate that the Active Learning method is able to increase student engagement in exercises so that they do not feel bored, thereby having a positive effect on improving physical fitness. Thus, the Active Learning method can be used as an effective alternative in teaching extracurricular sports activities, especially karate.